DAPATKAH UKURAN KAP MEMPENGARUHI AUDIT REPORT LAG DENGAN SPESIALISASI AUDITOR SEBAGAI PEMODERASI - Wukuf Dilvan Rafa; Muhsin; Tiya Nurfauziah (Universitas Palangka Raya, 2023)
This research aimed to analyze the effect of the variable kap size on audit report lag with auditor specialization as a moderating variable. The population in this research were mining companies listed on the indonesia stock exchange for the period of 2017-2019. Sample on this research was selected by purposive sampling method and order to obtain a 21 sample companies as 63 data analysis units. Hypothesit test in this research used of path analysis. Path analysis was an analytic on the research model that has been made previously. WarpPLS 7.0 was a software used in this research. The result of this research showed that kap size has a negative effect significant on audit report lag, auditor specialization was unable to moderate the relationship between kap size and audit report lag.